ABOUT REPETITION AND ITS MANIFESTATIONS IN LITERARY TEXTS - Ibragimova, Fazilat (Журнал иностранных языков и лингвистики, 2023)
Language, which is considered to be a magnificent and prestigious phenomenon, has many functions. Among these functions, the most recognized by linguists and literary scholars are the communicative function and the aesthetic function of language. The fact that it is a means of communication and interaction between people in society determines the communicative function of language, and the fact that it serves to express the mental state of a person, himself and his identity is the aesthetic function of language. The communicative feature of the language is manifested in the simple speaking style, scientific, official-publicistic styles, while the aesthetic function of the language appears more in connection with the artistic style. The aesthetic function of the language is manifested in the artistic text through linguopoetic means. In literary texts, various language units as a linguopoetic tool ensure the readability and effectiveness of the work, and the ideological and artistic maturity and thoroughness of the language of the literary work.